Rio 2016 Olympic Myths, Hard Realities - Zimbalist, Andrew (Brookings Institution Press, 2017)
A clear-eyed, critical examination of the social, political, and economic costs of hosting the 2016 summer OlympicsThe selection of Rio de Janeiro as the site of the summer 2016 Olympic Games set off jubilant celebrations in Brazil-and created enormous expectations for economic development and the advancement of Brazil as a major player on the world stage. Although the games were held without major incident, the economic, environmental, political, and social outcomes for Brazil ranged from disappointing to devastating.Rio 2016 assembles the views of leading experts on Brazil and the Olympics into a clear-eyed assessment of the impact of the games on Brazil in general and on the lives of Cariocas, as Rio's residents are known. Edited by sports economist Andrew Zimbalist, the other contributors include Juliana Barbassa, Jules Boykoff, Jamil Chade, Stephen Essex, Renata Latuf, and Theresa Williamson.